(untitled) (ACME, 2023)
This paper is a contribution to the theory of reverie of natural elements developed by Gaston Bachelard. It will argue that the contemplation of the sea elicits a peculiar look at the world that can affect our views of time and memory. After Heraclitus, the river is the major image for the unseizable passing of time; but the sea is where every river goes to. Thus, the sea becomes a perfect natural analogon for the conservation of the past in itself around which Henri Bergson built his theory of duration and memory: nothing really disappears, and the past has the consistence and lively eternity that traditional philosophy attributed to being. Literary intermediaries as well as a philosophical consideration of some recurrent images – especially wreckages and submerged cities – will help in the approximation of sea reverie to Bergson’s thought, that will be carried out in the conclusion.